Struktur Naratif Lakon Thothok Kerot Ki Harjito Mudho Darsono - Aziz, Abdul; Budiarti, Endah; Soeseno, B. Djoko (Wayang Nusantara: Journal of Puppetry, 2022)
AbstractThis paper aims to find the narrative structure of Thothok Kerot performance by Ki Harjito Mudho Darsono. The findings are similar to performance outlines. The research data were audio-visual recordings of Thothok Kerot performance by Ki Harjito Mudho Darsono. Structural method of Becker’s model has been used. In particular, Becker’s narrative structure simplified by Kasidi has been used in the analysis. It has been stated that the structure of a play is built hierarchically from three main parts according to the performance segmentation. Each shadow puppet performance is divided into three scenes, each scene has the same internal structure as a segment of one whole shadow puppet performance. The results show that the narrative structure of Thothok Kerot performance by Ki Harjito Mudho Darsono influences Surakarta style of shadow puppet performances.AbstrakTulisan ini bertujuan menemukan struktur naratif lakon Thothok Kerot Ki Harjito Mudho Darsono. Temuan itu dapat disetarakan dengan balungan lakon. Data penelitian berupa rekaman audio visual lakon Thothok Kerot Ki Harjito Mudho Darsono. Konsep struktur naratif Becker yang direduksi Kasidi digunakan dalam analisis. Konsep tersebut mengatakan bahwa stuktur lakon dibangun secara hirarkis dari tiga unit pokok sesuai dengan pembabakan lakon. Setiap lakon wayang dibagi ke dalam tiga babak, masing-masing babak memiliki stuktur internal yang sama sebagai suatu kesatuan lakon wayang secara menyeluruh. Metode yang digunakan adalah metode struktural model Becker. Hasil yang didapat yaitu struktur naratif lakon Thothok Kerot Ki Harjito Mudho Darsono terpengaruh pakeliran wayang kulit gaya Surakarta.